The Stages of Development of the Role of Women in Uzbekistan in the New Era - Ashurova Oyistakhon Yuldashevna (Zien Journals, 2022)
This artricle deals with the creation of a single electronic database aimed at improving entrepreneurial literacy and self-employment of young people and women, which includes measures, laws, and regulations on this topic, decision and intiatives.
Keywords: Enterpreneurship; women development; literacy